PERANCANGAN JARINGAN WIRELESS LAN DENGAN MENGGUNAKAN ROUTER OS MIKROTIK PADA SEKOLAH DASAR NEGERI PAHONJEAN 01 - kennedy, janero; Nur Rohman, Soleh (STMIK Komputama Majenang, 2019)
The background is a problem that occurs in al-Ittihad elementary school which causes the author to take the title of this thesis. . Around the Al-Ittihad Elementary School, the network signal from ISP providers, both GSM and CDMA, is not very good so that the data access received is not optimal. This is based on the author's own experience using GSM modems, surveys and interviews with teachers and school staff at Al-Ittihad Elementary School. Also faced with the fact that the high tariff for unlimited data access from the service provider PT. Telkom (speedy) made the author look for a solution, is there another way that is cheaper and simpler to be able to use the internet easily in the scope of this al-Ittihad elementary school comfortably, safely without having to worry about banned sites. The purpose and objective of the research is to first recognize and understand further computer network technology, especially wireless/wireless (wireless) networks. Both members make it easy for users to access the internet. Third, knowing the technique of making / building an infrastructure and implementation. Fourth, get to know information technology in the al-Ittihad elementary school environment. The research method is the method used by the author in the preparation of this thesis. The author uses methods and techniques to compile and present appropriate and accurate information. Therefore, appropriate methods and techniques are needed to obtain valid and accountable data. The method used by the author is as follows, the first research location. Second Collecting data and third Designing. Implementation is discussing how to install and configure the devices used in designing the WLAN network at the Al-Ittihad elementary school in Cilacap with Mikrotik. The output or results achieved in the design of this WLAN (Wireless Local Area Network) is to provide convenience for teachers, students and school visitors in accessing the internet, accessing the internet is not only in the school room but can also be accessed around the school environment via a wireless network. and does not require a data cable so that it is more efficient and effective.